Typhoid fever - Its prediction without Blood culture - Khan, Jahanzeb; Khan, Gulalai Wali; Khan, Muhammad Ali; Khan, Pervez (Journal of Postgraduate Medical Institute, 2011)
To diagnose typhoid fever on clijnical ground without blood culture, a study was conducted in Medcial A unit LRH, Peshawar on 25 patients with typhoid fever. 24(96%) blood cultures yielded the growth of salmonella typhi and 1 (4%)of S Parathphi A. Fever for more than 7 days was noted in 20 (80%) aptietns. Toxic look and coated lips were present in 17 days was cough with few basal crackles were recorded on 15(60%) cases. Spleen was enlarged in 15(60%) and pain abdomen with diarrhea were complained by 14(56%) patients. The TO and AO titres of the widal test were raised to > 1/320 in 16 (64%) cases. Clinical diagnosis of typhoid fever was suggested by the following 6 events: duration of fever for more than 7 days, toxic look and coated lips, dry cough with few crackles, soft spenomegally, pain abdomen with diarrhea and a positive widal test at screening dilution of > 1 / 320.